Fostering the Industrial Component of the European Green Deal: Key Principles and Policy Options - Simone Tagliapietra; Reinhilde Veugelers (Intereconomics)
Abstract The necessity to meet climate and environmental targets, while at the same time ensuring economic and social sustainability,requires a transformation that will generate enough benefits to compensate the losers.